2014
DOI: 10.5217/ir.2014.12.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Does Metformin Affect The Incidence of Colonic Polyps and Adenomas in Patients with Type 2 Diabetes Mellitus?

Abstract: Background/AimsColorectal cancer (CRC) develops from colonic adenomas. Type 2 diabetes mellitus (DM) is associated with a higher risk of CRC and metformin decreases CRC risk. However, it is not certain if metformin affects the development of colorectal polyps and adenomas. This study aimed to elucidate if metforminaffects the incidence of colonic polyps and adenomas in patients with type 2 DM.MethodsOf 12,186 patients with type 2 DM, 3,775 underwent colonoscopy between May 2001 and March 2013. This study enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 33 publications
0
42
0
2
Order By: Relevance
“…These effects are particularly intriguing for CRC because Peutz-Jeghers polyposis involves loss of LKB1, a tumor suppressor that also regulates AMPK. Metformin also appears to inhibit polyp formation and aberrant crypt foci (4042). …”
Section: Discussionmentioning
confidence: 99%
“…These effects are particularly intriguing for CRC because Peutz-Jeghers polyposis involves loss of LKB1, a tumor suppressor that also regulates AMPK. Metformin also appears to inhibit polyp formation and aberrant crypt foci (4042). …”
Section: Discussionmentioning
confidence: 99%
“…In fact, several recent studies have reported that cigarette smoking, obesity, and metabolic syndrome, as well as age and family history of CRC, are risk factors for colorectal neoplasm (CRN). [4][5][6] In particular, many previous studies have shown a consistent association between cigarette smoking and CRN risk. [7][8][9][10][11][12][13] However, most of these studies confirmed smoking as a risk factor for CRN through comparisons of never smokers to current or ex-smokers, and only some studies investigated the risk of CRN in detail according to the amount of smoking.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of cancer prevention, previous studies have investigated the preventive effect of aspirin, statins, metformin, and other medications used for other chronic diseases in the development of cancer and precancerous lesions, including colorectal adenoma. [7][8][9][10][11][12] Most patients with cancer are treated with chemotherapy with postoperative adjuvant or palliative aim. However, the effect of this chemotherapy on the precancerous lesions of many cancers is unknown.…”
Section: Introductionmentioning
confidence: 99%